Representação da narradora como experienciadora e dizente em Inés Del Alma Mía e na tradução para o português brasileiro: uma abordagem sistêmico-funcional - Hoy, Giovanna Marcella Verdessi (2017)
In this research, we aim to analyze the dynamism in the Ideational representation of the narrator and protagonist, Inés, in the role of Sayer and Senser in the parallel corpus of Inés del alma mía (ALLENDE, 2006) and in its translation to Brazilian Portuguese. The theoretical approach is the Systemic Functional Linguistics (HALLIDAY, MATTHIESSEN, 2004; EGGINS, 2002) on the interface of Translation Studies (CATFORD, 1965; HALLIDA, 2001; MATTHIESSEN, 2001; RODRIGUES-JÚNIOR and OLIVEIRA, 2015), and literary text (MONTGOMERY, 1993; SIMPSON, 1993; PAGANO, 2007; RODRIGUES-JÚNIOR and BARBARA, 2013). The data were submitted to the computing program called WordSmith Tools 6.0, specifically to the Word List, to the Concordance and the View & Aligner for organization and description. In the analysis of the female representations adopts the transitivity system of Systemic Functional Linguistics. In the comparison of these representations in the Source Text (SF) and in the Target Text (TT), chooses to the concepts of Ideational-shift and Ideational Equivalence (RODRIGUES-JÚNIOR and GARCIA de OLIVEIRA, 2015)) elaborated from the Catford (1968) studies and extended by Matthiessen (2001). Two hypotheses are proposed: i) the Mental and Verbal processes contribute to the dialogical and subjective dynamism in the representation of Inés, and; ii) although the Ideational Equivalences standards are more frequent, Ideational-Shift also will be found in the Ideational representation of Inés. The analysis shows that Inés is represented as a Sayer and Senser with a high degree of dialogical and subjective dynamism, making her a character capable to affect positively the community of which she belongs. It was also identified that, although Ideational equivalence has been the translator`s standard of choice, Ideational-Shift were also detected in elements of transitivity different of the Process. These changes occurred, for example, in the Circumstances that added information of mode, intensity, and time to the Inés' Ideational representation